MFP1 is a thylakoid-associated, nucleoid-binding protein with a coiled-coil structure - Jeong, Sun Yong (Oxford University Press, 2003)
Plastid DNA, like bacterial and mitochondrial DNA, is organized into protein–DNA complexes called nucleoids. Plastid nucleoids are believed to be associated with the inner envelope in developing plastids and the thylakoid membranes in mature chloroplasts, but the mechanism for this re-localization is unknown. Here, we present the further characterization of the coiled-coil DNA-binding protein MFP1 as a protein associated with nucleoids and with the thylakoid membranes in mature chloroplasts. MFP1 is located in plastids in both suspension culture cells and leaves and is attached to the thylakoid membranes with its C-terminal DNA-binding domain oriented towards the stroma. It has a major DNA-binding activity in mature Arabidopsis chloroplasts and binds to all tested chloroplast DNA fragments without detectable sequence specificity. Its expression is tightly correlated with the accumulation of thylakoid membranes. Importantly, it is associated in vivo with nucleoids, suggesting a function for MFP1 at the interface between chloroplast nucleoids and the developing thylakoid membrane system.